Nerve tissue engineering using blends of poly(3‐hydroxyalkanoates) for peripheral nerve regeneration. Issue 6 (7th July 2015) - Lizarraga‐Valderrama, Lorena R.; Nigmatullin, Rinat; Taylor, Caroline; Haycock, John W.; Claeyssens, Frederik; Knowles, Jonathan C.; Roy, Ipsita
<x xml:space="preserve">Abstract</x> The only types of polyhydroxyalkanoates (PHAs) that have been explored for use in nerve regeneration are poly(3‐hydroxybutyrate), P(3HB), and poly(3‐hydroxybutyrate‐co‐3‐hydroxyhexanoate) (P(3HB‐co‐3HHx)). However, nerve regeneration induced by these PHAs is inferior to that of autologous nerve grafting. The aim of this work was to study novel PHA blends as resorbable biomaterials for the manufacture of nerve guidance conduits. PHA blend films with varying ratios of poly(3‐hydroxyoctanoate)/P(3HB) (P(3HO)/P(3HB)) were produced using the solvent‐casting method. Neat films of P(3HO) and P(3HB), along with 25:75, 50:50, and 75:25 blend films of P(3HO)/P(3HB), were characterized with respect to chemical, material, and biological properties. On surface analysis, the blends exhibited higher values of roughness compared with the neat films. The differential scanning calorimetry characterization of the blends confirmed that P(3HO) and P(3HB) formed immiscible blends. FTIR and XRD analysis of the blends showed a decrease in crystallinity along with an increase of the proportion of P(3HO) . However, an increase in the stiffness of the blends was observed when the proportion of P(3HB) increased. Although all of the blends were biocompatible with NG108‐15 neuronal cells, the 25:75 P(3HO)/P(3HB) blend showed significantly better support for growth and differentiation of these cells. The mechanical properties of PHA blends correspond to the reported properties of peripheral nerves. Therefore, they could serve as base material for the manufacture of nerve guidance conduits.